A problem-focused approach to violence against women: The political-economy of justice and security programming - and Denney, Lisa; Domingo, Pilar (ODI, 2013)
The United Nations Commission on the Status of Women ended its 57th session on 15 March 2013 with an outcome document affirming the importance of eliminating violence against women (VAW). The Commission was unable, however, to achieve consensus on a global action plan. The negative reaction of some UN member states to an action plan is a worrying reminder of ongoing resistance to reform. These persistent challenges highlight the continuing struggle to gain a serious global commitment to address VAW and recognise it as a breach of women’s fundamental human rights. Engaging in this struggle, many donors have put addressing VAW generally, and in fragile and conflictaffected situations (FCAS) specifically, at the top of the development agenda and made it a major priority of international policy. But in practice progress remains difficult, not least due to entrenched resistance and discriminatory socio-political norms and gender relations that persist in many societies. The problem of violence against women therefore needs to be addressed from the perspective of the concrete socio-political and cultural conditions that shape its particular features and the relevant context specific dynamics of conflict, post-conflict patterns of violence and fragility. International efforts to support reform in the area of VAW in FCAS need to go beyond prescriptive approaches that focus on what access to protection, justice and redress should look like. We propose here an approach that engages with the specificities of the problem – paying attention to context, and the concrete political-economy dynamics of the drivers of VAW – and takes account of the real options that